Вопросы взаимовлияния популярной и джазовой музыки в Армении - Левоновна Малхасян, Ирина (Musical Armenia, 2010)
Musicologist, graduate student of Yerevan State Conservatory after Komitas Irina Levon Malkhasyan’s “Pop and jazz musics’ interaction questions in Armenia” article is considered in terms of music history, where the author represents the creative organizational and executional activities of famous musicians of that two areas in Armenia since 1950 to now in developing process. Interpretted with relative parallels, because it was formed and developed in Soviet era.